Synthesis of Multifunctionalized 2-Iminothiazolidin-4-ones and Their 2-Arylimino Derivatives - Le Corre, Laurent; Dasso Lang, Maria Chiara; Garbay, Christiane; Gravier-Pelletier, Christine; Busca, Patricia; Ethève-Quelquejeu, Mélanie; Braud, Emmanuelle (Synthesis, 2016)
Multifunctionalized 2-imino-3-(pyrazol-4-yl)thiazolidin-4-ones and 2-arylimino-3-(pyrazol-4-yl)thiazolidin-4-ones were prepared according to an efficient four-step procedure. The key step of the synthetic pathway involved the cyclization of 2-chloro-N-(pyrazol-4-yl)acetamide intermediate using KSCN or aryl isothiocyanate, respectively. The structure of the title compounds was confirmed on the basis of NMR data and 15N-labeling.
Keywords: thiazolidin-4-ones; pyrazoles; cyclization; heterocycles; regioselectivity